1967
DOI: 10.1071/bi9671169
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nutrients on Lysis of Fungal Hyphae in Soil

Abstract: Live fungal hyphae lyse faster in soil previously supplemented with glucose, peptone, or blood and bone meal than in non.supplemented soil. Whether or not the supplement increases the number of Actinomycetes or bacteria, either effect will result in more rapid lysis of hyphae. When peptone is added to soil which already contains fungal hyphae, Actinomy-cetes increase rapidly and the hyphae lyse. But with glucose as a supplement the fungus grows and coexists with the small increase in other microorganisms. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1969
1969
1981
1981

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…This may be explained by the very high numbers of bacteria and actinomycetes present in the soil at this stage [Figs;3(b) and 4(b)]. On the other hand, as previously suggested (Bumbieris and Lloyd 1967), fungi are able to grow and compete with other microorganisms provided that suitable nutrients are present in sufficient quantities. This explains the concurrent increase in the numbers of all four groups of microorganisms, especially in the glasshouse test where abundant nutrients would be provided by the growing pea plants.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…This may be explained by the very high numbers of bacteria and actinomycetes present in the soil at this stage [Figs;3(b) and 4(b)]. On the other hand, as previously suggested (Bumbieris and Lloyd 1967), fungi are able to grow and compete with other microorganisms provided that suitable nutrients are present in sufficient quantities. This explains the concurrent increase in the numbers of all four groups of microorganisms, especially in the glasshouse test where abundant nutrients would be provided by the growing pea plants.…”
Section: Discussionmentioning
confidence: 61%
“…In studies of the effect of various nutrients on mycolysis in soil, Bumbieris and Lloyd (1967) found that numbers of bacteria increased in soils supplemented with glucose, peptone, or blood and bone meal. Actinomycete numbers remained constant when glucose was added to soil but increased with peptone or blood and bone meal supplements.…”
Section: Introductionmentioning
confidence: 99%